CORRELATION OF PUBLIC PARTICIPATION AND PUBLICATION IN FORMING LEGISLATION - Irwansyah, Irwansyah; Marwan Hsb, Ali (NOMOI Law Review, 2024)
The formation of legislation is said to be participatory if there is public participation. However, public participation has so far only been procedural. However, after the Constitutional Court Decision Number 91/PUU-XVIII/2020 which stated that the formation of legislation must reflect meaningful participation consisting of the right to be heard, the right to be considered and the right to obtain an explanation. In order for this meaningful participation to run optimally, efforts are needed to optimize it. The method used in this paper is normative legal research with a prescriptive approach. Based on the research conducted, it was found that in order to optimize public participation to achieve meaningful participation, one of the main things that must be done is publication or openness of information, so that the public knows what material the contents of the legislation are being prepared and how far the formation process has progressed.